Synthesis and application of polyacrylamide hydrogels with incorporated acid-activated Laponite® for diagnosis of oncological diseases - Yu. M. Samchenko; O. A. Samoylenko; A. V. Verbinenko; I. I. Ganusevich; L. O. Kernosenko; T. P. Poltoratska; N. O. Pasmurtseva; O. O. Solovieva; I. I. Volobayev (Хімія, фізика та технологія поверхні, 2024)
Hydrogels with incorporated acid-activated Laponite® (LapA) platelets represent a new generation of biomaterials with promising biomedical application (e.g., diagnostics and therapy). The LapA nanomaterial have high specific surface area and demonstrate rather attractive hydrophilic properties. The physical cross-linking of hydrogels using the LapA allowed a significant improvement the systems homogeneity, transparency, and drug transport in these systems. In general incorporation of LapA may also affect the equilibrium degree of swelling at phase-transition from the swollen to the shrunken phase. In this work the effectiveness of using of polyacrylamide hydrogels (PAAG) with incorporated LapA for diagnosis of oncological diseases was studied. The synthesis procedure was performed using ultrasonication of aqueous dispersion of mixtures of monomer, crosslinking agent and initiators. The PAAG+LapA samples were characterized using SEM and PAAG swelling techniques. SEM images evidenced the presence of integration of LapA platelets into the hydrogel structure and formation of the shells of aggregated LapA particles. It can be explained by the formation of more active forms of LapA with stronger internal bonds. Effects of Lap, LapA concentration on the swelling kinetics and the maximal swelling degree were also evaluated. The the maximal equilibrium degree of swelling Qmax was reached within the first 5 hours. The concentration of platelets affected the value of Qmax, initially it decreased up to the minimum Qmax » 7.6 g/g at CLap » 0.04 % and then increased at higher concentrations. For these samples the protein separation spectrum of peripheral blood plasma was studied using the sodium dodecyl-sulfate polyacrylamide gel electrophoresis         (SDS-PAGE) technique. Peripheral blood plasma samples obtained from the donors, and colorectal cancer patients without distant metastases and with distant metastases were studied. The better separation of human plasma proteins was observed in hydrogels with incorporated LapA platelets. In future studies it is desirable to test these new       SDS-PAGE materials for diagnostics of different forms of cancer diseases.